A comparative study of Non-Colour Bank segment among leading paint brands in Asansol market - Singh, Samrat; Siddhanta, Somroop (Gyan Management Journal, 2023)
The Indian paint industry is one of the fastest growing ones in the country, maintaining double digit growth rates over the last few years, primarily due to shift in consumption patterns of the decorative paints. However, the Non-Colour Bank (NCB) segment consisting of enamels, primers, thinners, are not showing similar growth patterns, and is dominated by one firm. This study investigates the Availability, On-time delivery, Incentive schemes, and Customer Service pattern of Non-Colour Bank (NCB) products of Asian Paints Ltd., the market leader, and Other Brands, primarily including Berger Paints Ltd. in the Asansol Municipal Corporation area. The results will help Berger Paints, the market follower, to be aware of its position in the market while also assist other firms in finding out the lacunae regarding various NCB products in Asansol area in order to compete and have a strategic edge over other paint brands in the survey area.